Adaptive robust fault-tolerant control for a small size unmanned helicopter: Theory and experimental implementation - Ma, Aochen; Xian, Bin; Liu, Mohan; Yuan, Baokun; Jin, Xin (Aerospace science and technology, 2025)
This paper investigates the control design problem of small-size unmanned helicopter which is subject to unknown actuator faults. After an actuator failure occurs, the unmanned helicopter may become unstable and even lead to a fatal crash. Due to the complexity of the unmanned helicopter's mechanical structure and dynamics, there has been very few research work in the fault tolerant control design for unmanned helicopters, and only numerical simulation verification are provided. To address the power loss caused by tail rotor damage, a new sliding mode surface is proposed based on geometric control. And by combined with the adaptive control, a robust adaptive fault-tolerant control law is developed. It utilizes adaptive terms to approximate uncertain actuator's faults, and the robust components are used to improve the control law's robustness. This enables the small-size unmanned helicopter to complete normal flight missions even in the event of power loss failures. The proposed control algorithm's stability is proven using Lyapunov based analysis. To further demonstrate the control performance of this algorithm, validating experiments are conducted on a small-size unmanned helicopter control experimental platform, and good control performance is achieved under tail actuator faults. •Very few existing works have considered the fault tolerant control problem for the unmanned helicopter. Most research on fault-tolerant control are focused on quadcopter UAVs.•An adaptive law is designed to estimate the unknown actuator faults of the unmanned helicopter. A new robust fault tolerant control is developed.•The stability of the proposed control algorithm is proved, and asymptotic convergence of the helicopter's attitude tracking error is achieved.•The proposed fault-tolerant control strategy is experimentally validated on the self-build helicopter flight control platform while existing similar works only provide numerical simulation verifications.